1998
DOI: 10.1055/s-2008-1071230
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment in Primary Neonatal Megaureter

Abstract: The authors report their experience on 22 neonates (14 males and 8 females) with primary megaureter. In 18 patients a prenatal diagnosis was available, in the other four the diagnosis was suspected during a neonatal ultrasound screening. The dilatation involved the right ureter 7 times and the left 13 times, in 2 patients it was bilateral. Intravenous urography documented a type I ureteral dilatation in 2 renal units (8.3%), a type II in 9 (37.5%) and a type III dilatation in 13 (54.2%). Radionuclide scan (Tc9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 1 publication
0
18
0
1
Order By: Relevance
“…Moreover, it was revealed that the UNC patients had a more distinct dilatation of the ureter initially than the ''non-UNC'' group. For group 1 we determined 9 ± 3 mm (4-34) proximally and 7±3 mm (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) distally. The maximum pre-operative diameter of the 16 neoimplanted ureters later was 15 ± 3 mm (6-25) proximally and 15 ± 5 mm (6-23) distally.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was revealed that the UNC patients had a more distinct dilatation of the ureter initially than the ''non-UNC'' group. For group 1 we determined 9 ± 3 mm (4-34) proximally and 7±3 mm (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) distally. The maximum pre-operative diameter of the 16 neoimplanted ureters later was 15 ± 3 mm (6-25) proximally and 15 ± 5 mm (6-23) distally.…”
Section: Resultsmentioning
confidence: 99%
“…According to today's knowledge that a high percentage of the primary obstructive megaureters normalizes without impairment of renal function, the conservative approach is justified in severe asymptomatic cases too [1,3,15,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With modern ultrasound techniques, about 40% of POMs are discovered prenatally [6] and the fraction of symptomatic children decreased to 22-50% [7,8]. In the 1990s, several reports documented the high rate of spontaneous regression of prenatally diagnosed POM [7,[9][10][11][12][13]. Even though chronic renal failure has been described in rare cases of adults with bilateral POM [14], the lack of functional impairment of the great majority of kidneys with POM is an additional argument for taking a conservative approach [15].…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] CONCLUSION Primary megaureters should be categorized properly for the management purpose. Our case was without any reflux and obstruction and was treated conservatively in the beginning before the surgical intervention was contemplated.…”
mentioning
confidence: 99%